Back home - Davis, J. Frank (James Francis), 1870-1942 (Salt Lake City, UT : Project Gutenberg, 2024)
"Back Home" by J. Frank Davis is a fictional narrative written in the early 20th century. The book primarily revolves around themes of identity, regret, and reconciliation as it follows the journey of Captain James Carmichael of the Texas Rangers. He becomes entangled in the aftermath of a man's return to the United States after decades of living in exile due to a violent past. In the story, we meet Andrew Miller, a man with a scar who initially appears to be on a business trip but has a deeper, more dangerous motive in reconnecting with his past. Captain Carmichael encounters Miller on a train and later in San Antonio, where he observes the man$1 (Bs suspicious behavior related to another character, Wallace Locke. It becomes evident that Miller is not merely a stranger, but someone trying to navigate his troubled history while seeking to protect his daughter, Edith, from his past's dark revelations. As the plot unfolds, the tension rises, leading to an explosive confrontation, where themes of forgiveness and redemption come to the forefront, revealing the complexities of human experience against a backdrop of law and morality in the American Southwest. (This is an automatically generated summary.)s
Release date is 2024-05-08
Roger Frank and Sue Clark
Keywords: Short stories; Detective and mystery stories; Texas -- Fiction; Law enforcement -- Fiction; Texas Rangers -- Fiction